A Framework for Lean System Implementation in Healthcare - Ghosh, Dr. Manimay (Prabandhan: Indian Journal of Management, 2012)
Organizations are complex web of processes. When faced with process-related problems, it grapples to locate the source of the problem. Without proper identification of the source and its root causes, problem solving becomes a frivolous exercise. Problems keep recurring at regular intervals, and organizational members engage in patch working. Although extant literature is surfeited with articles on problem solving, yet many industry practitioners lack clear understanding on how to locate a problem and then resolve it. This article, which is a part of a major empirical research study conducted in a hospital, demonstrates the use of two well established tools: Value Stream Map (VSM) and A3